THE DOMESTIC HEALTHY FOOD INDUSTRY - THE INNOVATIVE WAY TO PROGRESS AND DEVELOPMENT - Сімахіна, Галина; Науменко, Наталія (SWorldJournal, 2025)
The crises caused by active combats in Ukraine are believed to be the serious threat for the civilians’ health, meanwhile the AFU military personnel accomplish their activity on the edge of physical and psycho-emotional capacities of a human. Therefore,